Pengaruh Faktor Pengetahuan dan Sikap Terhadap Kepatuhan Ibu Hamil dalam Mengkonsumsi Tablet Fe di Puskesmas Bogor Tengah - Gilang Purnamasari; Ani Margawati; Bagoes Widjanarko (Jurnal Promosi Kesehatan Indonesia, 2016)
ABSTRACTThe high death rate of mothers is a big problem in Indonesia. They died because of the great bleeding of anemia when they had pregnancy. At Bogor Tengah Puskesmas the prevalence of anemia of pregnant women is 63,63%. Whereas the scope of Fe 3 of pregnant mothers is 96.92%, it is related to the low compliance of pregnant women taking tablets Fe. The study aims to analyze the factor of knoeledge and attitude may be related to the compliance of pregnant women taking tablet Fe in the Bogor Tengah Puskesmas.This type of research is Explanatory Research with cross sectional approach, Subject of the study is all women in third semester of pregnancy at the Bogor Tengah Puskesmas, it is 53 women. The tool of collecting data is questionnaire. Data analysis in this research is the data analysis of univariate, bivariate data analysis with chi square. The result show that the most of respondent compliance consumption of tablet Fe is 60,4%. Multivariate analysis was not done because there is no related variables in this study. Public Health Center as the place closest to the public health service will need to provide information about important of taking tablet Fe to pregnant women through health promotion activities through Posyandu activities, ANC, class of pregnant women and health promotion activities that have been routinely implementedKeyword: Compliance, the pregnant mothers, tablet Fe